Probiotics therapy show significant improvement in obesity and neurobehavioral disorders symptoms - Cai, Yichen; Liu, Pan; Zhou, Xiaolan; Yuan, Jun; Chen, Qiu (Frontiers in Cellular and Infection Microbiology, 2023)
Obesity is a complex metabolic disease, with cognitive impairment being an essential complication. Gut microbiota differs markedly between individuals with and without obesity. The microbial–gut–brain axis is an important pathway through which metabolic factors, such as obesity, affect the brain. Probiotics have been shown to alleviate symptoms associated with obesity and neurobehavioral disorders. In this review, we evaluated previously published studies on the effectiveness of probiotic interventions in reducing cognitive impairment, depression, and anxiety associated with obesity or a high-fat diet. Most of the probiotics studied have beneficial health effects on obesity-induced cognitive impairment and anxiety. They positively affect immune regulation, the hypothalamic–pituitary–adrenal axis, hippocampal function, intestinal mucosa protection, and glucolipid metabolism regulation. Probiotics can influence changes in the composition of the gut microbiota and the ratio between various flora. However, probiotics should be used with caution, particularly in healthy individuals. Future research should further explore the mechanisms underlying the gut–brain axis, obesity, and cognitive function while overcoming the significant variation in study design and high risk of bias in the current evidence.